The Gap Between Legal Norms and Practice in Protecting Persons with Disabilities Against Employment Discrimination - Dwi Risky Ananda; Fatma Sari Ramadhani; Nasywa Kirana; Zahra Aulia Salma (Universitas Negeri Surabaya, 2026)
This article discusses legal protection for persons with disabilities in the employment sector in Indonesia. Law Number 8 of 2016 provides a strong legal foundation through the recognition of the right to work, protection from discrimination, accessibility, and affirmative policies in the form of employment quotas. However, this legal protection has not been effectively implemented in practice. The main challenges lie in weak implementation, lack of synchronization between regulations and implementing policies, and the government’s limited attention to the economic and educational aspects of persons with disabilities. As a result, persons with disabilities still face barriers in obtaining equal employment opportunities. Therefore, strengthening legal protection requires more effective implementation through policy harmonization, enhanced supervision, and the provision of reasonable accommodation to ensure equality in the workplace